La comunicación en el ejercicio de los derechos de participación y ciudadanía - Contreras Martínez, Erika Lissette (2019)
While it is true, communication is a very essential tool to survive and communicate with the rest of the world, a way to express what we feel or how we feel, which is part of the development of humanity to know other cultures, know more about them such as their habits, beliefs, religion, routine, etc. Also, it is stated that citizen participation is exalted to the Greek systems, where the dimension of the possibility of gathering an assembly of citizens with fullness of rights, with the capacity to go reciprocally, among others. The purpose is to know the level of communication that the inhabitants have in order to implement communication Tips so that they can freely exercise citizen participation, these are self-limiting because they feel the fear of being wrong in Their views or that they will do rejected because they believe that their views will be overlooked to others.